Enhancing the Efficiency of Pig Production by Utilizing Advanced Breeding Techniques - Wang, Yuran (Transactions on Environment, Energy and Earth Sciences, 2024)
Since the farming society, people have begun to cultivate land and raise animals at the same time to provide a stable source of food. As one of the earliest animals raised by humans on a large scale, pigs are still the most purchased meat per capita today, occupying a large part of animal husbandry system. In modern animal husbandry, pig breeding is of utmost importance, as it relates to pork production and quality, as well as the economic benefits of the livestock industry.  Selection, genetic marker technology and gene editing techniques assist in pig breeding, such as removing key genes that contribute to the pathogenicity of PRRS viruses. In this paper, after analyzing the stress resistance of different pig breeds, it was found that local pig breeds have potential advantages in disease-resistant breeding research. Crossing them with introduced pig breeds can improve production performance and economic benefits. These research achievements not only provide a scientific basis for pig breeding but also offer new directions for the genetic improvement of global pig breeds and the development of new breeds, thus promoting the sustainable development of the animal husbandry industry.